Religion as critique : Islamic critical thinking from Mecca to the marketplace - Ahmad, Irfan, 1974- (Chapel Hill : The University of North Carolina Press, 2017)
"Irfan Ahmad makes the far-reaching argument that potent systems and modes for self-critique as well as critique of others are inherent in Islam--indeed, critique is integral to its fundamental tenets and practices. Challenging common views of Islam as hostile to critical thinking, Ahmad delineates thriving traditions of critique in Islamic culture, focusing in large part on South Asian traditions. Ahmad contemplates and interrogates Greek and Enlightenment notions of reason and critique, and he notes how they are invoked in relation to "others," including Muslims. Drafting an alternative genealogy of critique in Islam, Ahmad reads religious teachings and texts, drawing on sources in Hindi, Urdu, Farsi, and English, and demonstrates how they serve as expressions of critique. Throughout, he depicts Islam as an agent, not an object, of critique."--
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed November 21, 2017).
Added to collection customer.56279.3
Keywords: Islamic philosophy; Faith and reason -- Islam; Critical thinking; Criticism; Reasoning; Critical thinking; Criticism; Faith and reason -- Islam; Islamic philosophy; Reasoning; PHILOSOPHY / Eastern; Electronic books